Eksistensi Pemberlakukan Pidana Adat Bagi Masyarakat Di Luar Hukum Adat - Shavira Hermala Meidy (Widya Yuridika, 2022)
Before the implementation of the Criminal Code in Indonesia, in several regions in Indonesia there was a norm that became the law and regulations that bind the behavior of local people known as customary law. Customary law has provisions that must be obeyed and cannot be violated by indigenous peoples. If a violation occurs in the future, it will be subject to customary sanctions. It should be understood that customary law is law that applies in certain areas, therefore the application of customary law can be used for certain areas in accordance with customary provisions. The application of customary law is not only for indigenous indigenous peoples but also for individuals who are outside the customary area if they violate local customary regulations. Taking into account the circumstances above, the formulation of this problem is regarding the application of customary law for non-customary communities.